Blended Ghost Force Correction Method for 3D Crystalline Defects (Communications in Computational Physics, 2021)
Atomistic/continuum coupling method is a class of multiscale computational method for the efficient simulation of crystalline defects. The recently developed blended ghost force correction (BGFC) method combines the efficiency of blending methods and the accuracy of quasi-nonlocal (QNL) type methods. BGFC methodcan be applied to multi-body interaction potentials and general interfaces. In this paper, we present the formulation, implementation and analysis of the BGFC method inthree dimensions. In particular, we focus on the difference and connection with otherblending variants, such as energy based blended quasi-continuum method (BQCE)and force based blended quasi-continuum method (BQCF). The theoretical results arejustified by a few benchmark numerical experiments with point defects and microcrack in the three dimensional face-centered cubic (FCC) lattice.